On the dynamics in the southeastern Ligurian Sea in summer 2010. (15th May 2020) - Poulain, P.-M.; Mauri, E.; Gerin, R.; Chiggiato, J.; Schroeder, K.; Griffa, A.; Borghini, M.; Zambianchi, E.; Falco, P.; Testor, P.; Mortier, L.
Abstract: Drifters and a glider were operated in the southeastern Ligurian Sea to study the near-surface currents and water mass properties in summer 2010. Additional data were collected by a moored current meter in the Corsica Channel (CC). These in situ data were complemented by surface wind products, satellite images of ocean color and a Regional Ocean Modeling System (ROMS) numerical model that was implemented to simulate the local coastal dynamics. Southward currents were prevailing along the continental Italian coast, advecting filaments with a high optical signal coming from the Arno River. North of Elba Island, currents turned westward and northward in the vicinity of the CC. Further to the north they veered eastward, forming an anticyclonic circulation feature centered around Capraia Island. This general circulation picture was disrupted and reversed during events of sustained southerly winds occurring with a period of about a week. The near-surface currents in the CC and the anticyclonic circulation around Capraia Island showed the same weekly variations related to the local wind forcing. The ROMS model simulations agreed satisfactorily with the observations, in particular the strength of the Capraia anticyclonic circulation (quantified with the Capraia index) was confirmed to be strongly wind-dependent. Highlights: The surface circulation in the southeastern Ligurian Sea is strongly wind-dependent. Anticyclonic circulation around Capraia Island is predominant. Currents transport offshore filaments of low-salinity and nutrient-rich waters of riverine origin.